2012
DOI: 10.1534/g3.112.004093
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of PDZ Domain-Encoding Genes in Drosophila Border Cell Migration

Abstract: Cells often move as collective groups during normal embryonic development and wound healing, although the mechanisms governing this type of migration are poorly understood. The Drosophila melanogaster border cells migrate as a cluster during late oogenesis and serve as a powerful in vivo genetic model for collective cell migration. To discover new genes that participate in border cell migration, 64 out of 66 genes that encode PDZ domain-containing proteins were systematically targeted by in vivo RNAi knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 88 publications
0
30
0
Order By: Relevance
“…In vivo gain and loss of function of ephrin‐B1 demonstrate that ephrin B1 plays a crucial role in migration of pyramidal neurons to the cerebral cortex (Wu et al, ; Dimidschstein et al, ). Furthermore, targeting a selected class of genes by RNAi reveals that PDZ domain‐encoding genes such as cnk are involved in border cell migration in Drosophila (Aranjuez et al, ). Incorrect neuronal migration can cause several brain malformations and cognitive dysfunction (Gleeson & Walsh, ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo gain and loss of function of ephrin‐B1 demonstrate that ephrin B1 plays a crucial role in migration of pyramidal neurons to the cerebral cortex (Wu et al, ; Dimidschstein et al, ). Furthermore, targeting a selected class of genes by RNAi reveals that PDZ domain‐encoding genes such as cnk are involved in border cell migration in Drosophila (Aranjuez et al, ). Incorrect neuronal migration can cause several brain malformations and cognitive dysfunction (Gleeson & Walsh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we performed an RNA interference (RNAi) screen targeting PDZ domain-containing genes to identify regulators of border cell collective migration 40 , which provided a starting point to identify candidate GBM migration genes. Proteins that contain the PDZ proteinprotein interaction domain facilitate the formation of multi-protein scaffolding complexes with conserved roles in signaling, cell polarization, and adhesion, making them excellent candidates to regulate the collective migration of normal and cancer cells.…”
Section: Identification Of Candidate Csc Invasion Genes Via Border Cementioning
confidence: 99%
“…Proteins that contain the PDZ proteinprotein interaction domain facilitate the formation of multi-protein scaffolding complexes with conserved roles in signaling, cell polarization, and adhesion, making them excellent candidates to regulate the collective migration of normal and cancer cells. The majority of Drosophila PDZ-(PSD95/Dlg/ZO1-) domain genes were screened for the ability to promote border cell migration 40 (Fig. 3a).…”
Section: Identification Of Candidate Csc Invasion Genes Via Border Cementioning
confidence: 99%
“…Recently, we performed an RNA interference (RNAi) screen targeting PDZ domain-containing genes to identify those that regulate border cell collective migration 42 , which provided a starting point to identify candidate GBM migration genes. Proteins that contain the PDZ protein-protein interaction domain facilitate the formation of multi-protein scaffolding complexes with conserved roles in signaling, cell polarization, and adhesion, making them excellent candidates to regulate the collective migration of normal and cancer cells 43,44 .…”
Section: Identification Of Candidate Csc Invasion Genes Via Border Cementioning
confidence: 99%
“…We and others recently showed that inhibition of the Drosophila Rap1a homolog (Rap1) disrupted migration to the oocyte due to defects in actin-rich protrusions and altered cell-cell adhesion 57,58 . Rap1a is also regulated by the screen multi-hit gene, PDZ-GEF 42 (ortholog of human RapGEF2/PDZ-GEF1 and RapGEF6/PDZ-GEF2; Supplementary Table 1).…”
Section: Rap1a Levels Are Elevated In Gbm Patients and Correlate Withmentioning
confidence: 99%